Effective anti-corruption policy-making: What can we learn from experimental economics? - Amadou Boly; Robert Gillanders (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2017)
Experimental studies have shown that deterrence (monitoring and punishment) can be an effective anti-corruption policy. Even when they themselves stand to lose, policymakers may enact deterrence policies with real teeth ... However, policymakers' legitimacy is crucial: a given deterrence policy is more effective when chosen by an honest policymaker as opposed to a corrupt one.
Keywords: 330